(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The research aims to identify the tax policy strategy adopted in Iraq after the change of the tax system in 2003 and beyond, and then make a comparison of the two strategies on corporate data whether they are charged with progressive tax rates and after the change of the system as the tax rates became fixed, and then indicate the changes In the tax proceeds, and knowing the dimensions of the approved tax policy, is it a tax reform strategy or a strategy to attract investments. The research started from the problem of exposure of the Iraqi tax system to several changes in the tax strategy from 2003 until now, as this led to a reflection on the technical organization of taxes, in terms of the tax exemption.And these many amendments to the tax system have a significant impact on tax revenue and tax justice, as well as leaving a clear impact on the distribution of the tax burden among the different types of companies, even if the direct withholding taxes.In order to achieve the goal of the research, the deductive approach was chosen in presenting the theoretical side, but in the practical side, the descriptive analytical approach was chosen to study the actual reality of the data. Working with it in relation to the fixed tax rate, and this is not what was claimed as a tax reclamation strategy, but rather it was a foreign investment entry strategy.The research based its most important recommendations on reconsidering the corporate tax rate and raising the tax rate in proportion to the increase in tax revenues